Faktor-faktor yang mempengaruhi keandalan dan ketepatan waktu pelaporan keuangan pada Organisasi Perangkat Daerah Kabupaten Sumbawa Barat - Miharja, Een Samawati; Handajani, Lilik; Furkan, Lalu M. (Universitas Sam Ratulangi, 2020)
This study aims to provide empirically the effect of the human resources quality, utilization of information technology, accounting internal control, and financial control on reliability and timeliness of financial reporting on Local Government of West Sumbawa. The sample of this study is 76 respondents that work as civil servants at finance departments of 38 units at Local Government of West Sumbawa which taken by purposive sampling. This study shows that human resources quality, internal control of accounting, and financial control have positive and significant effect on reliability of financial reporting. This study also reports that human resources quality, utilization of information technology, accounting internal control, and financial control do not have effect on timeliness of financial reporting. On those findings, this study implies that the agency theory is consistent with the efforts of Local Government of West Sumbawa in term to present reliable financial information. Otherwise, this study implies that the compliance theory is not applicable to Local Government of West Sumbawa as human resources quality, utilization of information technology, accounting internal control, and financial control are not as determinants of timeliness on their financial reporting.